Analysis of Risk Factors for 24 Patients With COVID-19 Developing From Moderate to Severe Condition - Li, Dianming; Liu, Chuanmiao; Liu, Jiahui; Hu, Junfeng; Yang, Yanli; Zhou, Yufu (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: The present study aimed at investigating the clinical risk factors for COVID-19 patients developing from moderate condition to severe condition, and providing reference for early intervention and prognosis. Methods: We collected the clinical data of 24 patients with moderate-to-severe COVID-19 who were admitted to the isolation ward of the First Affiliated Hospital of Bengbu Medical College from January, 2020 to February 20, 2020, and evaluated the data of clinical characteristics, blood test results, inflammatory index, chest CT imaging characteristics, and antiviral treatment, comparing this with the clinical data of 41 patients with moderate condition in the same period. From this comparison we thus summarized the current knowledge of potential risk factors for COVID-19 patients developing from moderate to severe condition. Results: (1) Clinical characteristics: The moderate-to-severe group and the moderate group in terms of combined common underlying diseases and respiratory frequency showed significant difference statistically (t-value were 13.32, 6.17, respectively, P < 0.05), while no significant difference between the two groups in gender, age, or clinical symptoms was statistically observed(P > 0.05). (2) Analysis of blood test results: The lymphocyte count and plasma albumin of the moderate-to-severe group were significantly lower than those of the moderate group (t-values were 4.16, 4.11, respectively, P < 0.05), and the blood glucose and urea of the moderate-to-severe group were significantly higher than those of the moderate group (t-value were 3.27, 4.19, respectively, P < 0.05). However, there was no significant difference in terms of white blood cell count (WBC), platelet count (PLT), and glutamic-pyruvic transaminase (GPT) (P > 0.05). (3) Comparison of inflammatory indicators: The level of IL-6 and CRP of the moderate-to-severe group were significantly higher than those of the moderate group (t-values were 2.84, 4.88, respectively, P < 0.05). (4) Imaging comparison: As for patients with moderate COVID-19, the imaging manifestations were the concurrence of ground-glass opacity, patchy shadow, and consolidation shadow in both lungs, diffuse ground-glass opacity in both lungs accompanied by air bronchogram, and large area consolidation of both lungs with pulmonary interstitial changes. The possibility for these patients to develop into severe condition increased, and the differences were statistically significant (t = 10.92, P < 0.05). (5) Clinical antiviral treatment: There was no statistically significant difference in the combination of two or three antiviral drugs between the two groups (χ2 = 0.05, P > 0.05). Conclusion: Current evidence suggested that the combination of common underlying diseases, respiratory frequency, lymphocyte count, blood glucose, albumin, urea level, inflammatory factors (CRP, IL-6), and imaging manifestations collectively contributed to the potential risk factors for the development of COVID-19 from moderate condition to severe condition. Particular attention should be paid to early detection and intervention during clinical work, which will be of vital significance to the ascent of the recovery rate as well as the reduction of mortality.